The The Role of Energy Consumption, FDI, and HDI in Economic Growth: A Panel Data Analysis - Okta Dian Sari; Winda Fuji Lestari (TECHNOBIZ : International Journal of Business, 2026)
This study aims to examine the impact of energy consumption, foreign direct investment, and the Human Development Index on economic growth in ASEAN countries, namely Indonesia, Malaysia, Thailand, the Philippines, and Vietnam, over the period 2010–2023. Using panel data and the Fixed Effect Model (FEM) estimation method, the results indicate that all three independent variables have a significant effect on economic growth. The findings of the Chow test and Hausman test support the selection of the FEM as the most appropriate approach for explaining variations across countries and over time. These results underscore that increases in energy consumption, foreign direct investment, and the Human Development Index are strategic factors in promoting economic growth in the ASEAN region.